Evaluating Business Policies and Strategies for Competitive Advantage in Rwanda’s Fintech Sector: A Case Study Approach (International Journal of Scientific Research and Management (IJSRM), 2024)
This study was carried out with the general objective of evaluating the business policies and strategies employed by fintech companies in Rwanda in ordered to gain and sustain a competitive advantage in the market. The study was guided by three objectives that include: To find out the current business policies and regulatory frameworks affecting the competitive positioning of the fintech companies in Rwanda; To examine the strategies fintech companies in Rwanda are employing to differentiate themselves and achieve sustainable competitive advantage in the market; and To assess the challenges and opportunities fintech companies face in implementing these strategies, and provide recommendations for improving their competitive edge in Rwanda’s fintech sector. The study was guided by two theories (Competitive Advantage Theory and Resource-Based View). The research design that was adopted for this study was a descriptive research design. In relation to the target population, only those employees involved in key decision-making process in the fintech companies were the only ones who were considered adding to 150 employees picked from the departments (operations, marketing, and compliance). A questionnaire that was structured and rated in a likert scale was used as the instrument of collecting data. The multiple regression analysis did show that, Current Business Policies and Regulatory Frameworks (β = 0.276, p < 0.01) had a positive and significant effect on competitive advantage. Also, Strategies for Differentiation (β = 0.426, p < 0.01) had the strongest positive influence on competitive advantage. Finally, Challenges and Opportunities (β = 0.355, p < 0.01) also had a significant positive effect on competitive advantage. The study has a conclusion that business policies and regulatory frameworks in Rwanda, have an impact that is positive on the fintech firms’ competitiveness. Differentiation strategies that have centered on digital transformation and innovation are the most influences of sustainable competitive advantage of fintech firms. The study also concludes that despite the fact that there are challenges that befall the fintech firms like the shortage of funding and stiff competition from the traditional financial institutions, they can leverage opportunities like high mobile penetration and government support to strengthen their market position. The study underscores the importance of aligning regulatory policies with fintech innovation and providing fintech firms with the resources needed to implement their growth strategies effectively.